Heat stress assessment among workers working at palm oil plantations in Muadzam Shah, Pahang - Nurul Maisarah, Mohd Isa (2017)
A cross sectional comparative study had been conducted to investigate the effect of exposure to heat among workers working at palm oil plantation in Pahang. A total number of 44 respondents involved in this study. A Wet Bulb Globe Temperature (WBGT) and Anemometer were used to measure air humidity, radiant heat, ambient air temperature and wind speed. Next, a digital oral thermometer was used to measure personal core body temperature. To determine the prevalence of heat stress symptoms, a standardized set of questionnaire was adapted form (Hunt, 2011). Result shows mean value for air humidity , radiant heat, ambient air temperature and wind speed among exposed and unexposed group were (exposed: 33.7°C, unexposed 29.8°C), (exposed: 46.7°C, 37.0°C), (exposed: 27.6°C, 28.4°C) and (exposed: 1.150m/s, unexposed: 1.154m/s) respectively. There were a significant difference for ambient air temperature (p≤0.05) and radiant heat level (p≤0.001) among exposed and unexposed. Mean value for body core temperature among respondents were 36.6°C for exposed and 36.4°C for non-exposed group. Result from the t-test analysis shows that, there was no significant difference for core body temperature among respondents. The highest frequency of health illness symptoms experienced by respondents were headache (72.7%), followed by dizziness (65.9%), fatigue (50.0%), and red rash on skin (38.6%). Findings revealed that, exposed group having the highest number of symptoms for headache, fatigue, dizziness, and red rash on skin. Environmental Heat Stress Index had been calculated for both working areas. Results revealed that, Heat Index for working environment for exposed group was higher compared to non-exposed with the reading of 37°C for exposed and 34°C for non-exposed. From the heat stress index chart, all respondents were at risk on developing heat stress illness since the level of Heat Index for their working environment was in the yellow zone. In conclusion, findings from this study confirmed that the exposed group pose a higher risk in developing heat stress illness and symptoms due to the exposure of working environment to heat while performing task.